Sustainable seawater desalination in marine protected areas: Modelling and monitoring activity - Mossa, Michele; De Padova, Diana (Plurimondi; No 22 (2025): War and peace, 2025)
This manuscript presents numerical simulations of the discharge from a desalination plant planned within a Marine Protected Area characterized by increasing freshwater demand. The modelling activity investigates the potential impacts of brine release on the coastal marine environment, with the aim of supporting environmentally sustainable design solutions. The proposed system adopts mitigation strategies based on the mixing of brine with treated wastewater, allowing the assessment of different dispersion scenarios under representative winter and summer hydrodynamic conditions. Results indicate that salinity variations remain limited and largely confined near the seabed, suggesting negligible effects on sensitive benthic habitats. The study highlights the role of green desalination solutions, supported by numerical modelling, as an effective approach to reconcile local water supply needs with the conservation of marine ecosystems in protected coastal areas.